Cross-Cultural Transition and Psychological Adaptation of International Students: The Mediating Role of Host National Connectedness - Bethel, Alicia; Ward, Colleen; Fetvadjiev, Velichko H. (Frontiers in Education, 2020)
Abstract Cross-cultural transitions are challenging and often have detrimental consequences for psychological well-being. This is particularly true for international students at tertiary institutions who are not only transitioning between school and higher education, but also between vastly different educational systems. This study tests a predictive model of psychological adaptation with international students whereby host national connectedness mediates the effects of personal resources and contextual factors on adaptive outcomes. A sample (N = 1527) of international tertiary students in New Zealand completed a survey that measured self-reported English language proficiency, perceived cultural distance, perceived cultural inclusiveness in the classroom, host national connectedness (defined by frequency of contact, number of friends, social support, and general belongingness), life satisfaction and psychological symptoms. Path analysis indicated that host national connectedness fully mediated the effects of English language proficiency on psychological symptoms and partially mediated the effects of language proficiency, cultural distance and cultural inclusion in the classroom on life satisfaction and psychological symptoms. The findings highlight the importance of international students’ relationships with host nationals, and the results are discussed in relation to strategies that could enhance student-host connectedness during cross-cultural transitions.